(untitled) (Bangladesh Journal of Agricultural Research, 2026)
The study was conducted at summer tomato growing areas in Jashore and Satkhira districts of Bangladesh to describe the insecticide use pattern on summer tomato production. Ninety farmers were selected randomly and an interview schedule was developed according to the objective of the study. Farmers of the study area used 16 different types of pesticides and most of them were toxic. In the study area 77.77% of the farmers sprayed insecticides on summer tomato one or more than one times in a week, 82.2% of the farmers harvested their crop at 0-5 days after spraying, 31.1% of the farmers depended on pesticide dealer for insecticide related knowledge, maximum farmers (84.4%) mixed different types of insecticides during spraying, most of the farmers (65.6%) measured insecticides approximately, 73.3% of the farmers started 1st spray without observing any insect in the field and 51.1% of the farmers didn’t use any safety measures during spraying insecticides. Farmer’s education, farm size annual income, training experience had negative relationship with the schedule of insecticide spray and positive relationship with the harvesting time after insecticide spray, use of tools for measuring pesticide, use of safety method where most of the relationships were significant. Bangladesh J. Agril. Res. 48(3): 349-357, September 2023